Vascular Malformations - Neetu Bhari; Akash Agarwal; C. V. V. Asritha; Maitreyee Panda; Rahul Mahajan (Wolters Kluwer Medknow Publications, 2024)
Vascular malformations are intricate anomalies of the circulatory system, presenting a diverse array of clinical manifestations, and posing significant challenges in diagnosis and treatment. The pathogenesis of vascular malformations is explored through the lens of genetic and molecular mechanisms, shedding light on the pivotal role of somatic mutations and dysregulated signaling pathways. Clinical presentations of vascular malformations are widely variable, ranging from cosmetic concerns to life-threatening complications. The utility of imaging techniques, such as magnetic resonance imaging (MRI), computed tomography (CT), and angiography, are discussed in detail, emphasizing their role in precise delineation and characterization. Therapeutic strategies for vascular malformations are multifaceted, considering factors such as lesion size, location, potential complications, and patient-specific factors. Traditional interventions, including surgical excision and embolization, are appraised alongside emerging approaches like targeted molecular therapies and minimally invasive procedures. The manuscript underscores the need for an individualized treatment approach, optimizing outcomes while minimizing risks and complications. In summation, this manuscript offers a comprehensive analysis of vascular malformations, encompassing their underlying pathogenesis, clinical nuances, diagnostic methods, and therapeutic considerations. By synthesizing current knowledge and highlighting gaps in understanding, this review serves as a valuable resource for clinicians, researchers, and medical practitioners, fostering an enhanced comprehension of vascular malformations and paving the way for improved patient care and innovative research endeavors.